The model of reproductive system - Švitra, Donatas; Grigolienė, Rasa (Lietuvos matematikos rinkinys, 1998)
The aim of the work is to create a mathematical model of the dynamics of estrogenic hormones. The characteristics of the physiology of female reproductive system, hormonal reguliation of the ovulatory cycle: feedbacks in the system "pituitary—gonads" are described. It is shown a schematic representation of the pituitary—gonads circuit, on wich base the mathematical model is proposed. The mathematical model consists of 6 nonlinear differential equations with time delay.